Design of high power density isolated DC-DC converter - Tan, Jia Hui (2016)
The fast development in the Internet of Things (IoT) and cloud computing have caused a greater demand of server power supplies. In this project, the focus is designing an Isolated DC-DC converter to improve on the power areas by reducing the pressure on the data servers when delivering sufficient amount of power for the rising needs. Several SMPS resonant topologies to develop an isolated DC-DC converter such as Series-Resonant, Parallel-Resonant, LCC Resonant and LLC Resonant were researched and discussed. LLC Resonant Converter topology was adopted. LLC resonant topology has the capability of reducing switching losses of the MOSFETs with wide input voltage range, and achieving high power density and efficiency of the converter. This isolated DC-DC converter consists of several stages, mainly the switching network, LLC resonant tank, full-wave rectifier and an output filter. The DC-AC section includes a switching network which uses rectangular pulses from a PFM-technique controller to switch the two power MOSFETs simultaneously. The LLC resonant tank ensures the resonant frequency is in the ZVS region to reduce switching losses as high power density and efficiency are the focuses of this project. In AC-DC section, a full-wave rectifier converts the AC waveform from the transformer back into a DC output voltage and an output filter would eliminate the voltage ripples and noises to provide a stable supply for the servers. The main features of this circuit compared to the other designs is that the selection of the power MOSFETs in the switching network which could supports high input voltage up to 500V and high switching frequency of 200 kHz. The simulation results of the isolated DC-DC converter were obtained and analysed. It is designed with a high input voltage of 380Vdc and a 12.8Vdc and 15.8A at the output of the converter. A total output power of 202.24W is obtained with a high efficiency of 94.5% during the software simulation. A software simulation model of the isolated DC-DC converter with result is presented.